THE EFFECT OF USING FONDI APPLICATION ON STUDENTS’ SPEAKING SKILL - Qirani, Dirsa; Batau, St Haliah; Rampeng, Rampeng (Lembaga Jurnal FKIP Universitas Bosowa, 2025)
This study aims to analyze the effect of using Fondi application on students’ speaking skill at SMP Kemala Bhayangkari Makassar. The focus is on understanding how digital tools can influence language acquisition in a classroom setting. This research employed a quantitative method with a pre-test and post-test design. The subject of this study consist of 33 eight-grade students, whose speaking skill were assessed before and after using the Fondi application over a specified period. The results indicate a significant improvement in students’ speaking skill, with the average of pre-test score increasing from 48.18 to 82.42 in the post-test. These findings suggest taht the Fondi application is effective in enhancing students’ speaking skill and creating a more supportive learning environment.